Sourdough authentication: quantitative PCR to detect the lactic acid bacterial microbiota in breads - Pontonio, Erica (Sci Rep, 2017)
No national legislation anywhere in the world regulates and protects traditional/typical sourdough breads. Sourdough fermentation is firmly associated with a century-old tradition, and with sensory and nutritional quality of breads. A well-defined cell density of lactic acid bacteria has to be reached at the end of fermentation, and be indirectly detectable in baked breads. A Quantitative PCR (qPCR) method was developed to discriminate between breads made with and without sourdoughs. Universal primers targeting an approximately 178-bp fragment of the 16S rRNA-encoding gene of lactic acid bacteria were designed, covering the known diversity of sourdough lactic acid bacteria and excluding commonly encountered flour bacterial contaminants. A total of 191 breads either made with traditional type I and dried sourdough and baker’s yeast, or by a chemical leavening method were shown to be accurately discriminated by means of qPCR. Discriminating values of gene copy number were only weakly correlated with pH values, and with lactate and acetate concentration, thus questioning the validity of these latter indirect indices. The use of sourdough has to be guaranteed to meet both bakery and consumer expectations, and to fulfil legal requirements; our work presents a reliable authentication method providing a suitable tool to satisfy such requirements.